Species Composition and Assessment of Sphingidae in Mt. Agad-Agad, Iligan City, Philippines - Romeo Jr. Rogano Patano; Alma B Mohagan; Maria Melanie M Guiang; Fulgent P Coritico; Honey Christine T Anches; Hanah Gloricel H Jebulan; Erl Pfian T Maglangit; Victor B Amoroso; Olga M Nuñeza (Journal of Tropical Life Science, 2022)
Sphingidae (Hawkmoth or Sphinxmoth) is a known bioindicator that is naturally affected by environmental issues such as deforestation and pollution. Members of thisfamily are widely distributed in Southeast Asia and play vital roles as indicators ofhabitat quality and biomass degradation. This study highlights the diversity and assessment of hawkmoths of Mt. Agad-Agad (Sitio Langinlanon, Barangay Puga-an)on Iligan City. Two sampling stations were established, the upper and lower Mt.Agad-Agad. Light trap sampling using 2 × 3 m2 white silk cloth and 500 watts lightbulb was established in selected points of the sampling stations. Six species belonging to four genera were recorded of which two species, Acosmeryx socrates and Polyptychus trilineatus philippinensis, were found very rare in the area. Station 2 (lowerMt. Agad-Agad) had the highest number of species recorded compared to Station 1(upper Mt. Agad-Agad). However, there is no significant difference between the two(t=0.59, critical t=2.2281, p=0.56) sampling stations in terms of species composition. Moreover, two species from the genus Ambulyx are the endemic species observed, viz, A. bakeri and A. wilemani.